PERANCANGAN SET FURNITURE UNTUK AREA SANTAI DI PERPUSTAKAAN UNIVERSITAS SURABAYA - Juventa Juventa; Elieser Tarigan; Audit Yulardi (CALYPTRA, 2018)
Abstract –While in the library, the visitors will spend time to studying, reading books, or doing the tasks. For those who spend time in the library in a long time, certainly would not be comfortable if continue to sit in a chair with a difficult position to change. Therefore will be provided area that can make visitors comfortable and do not feel tired when in the library. The area is a lounge area, where visitors can study, read books, or do the task with a sitting position on the floor. To do these activities, then required some furnitures for the lounge area, table for ‘lesehan’ and a bookshelf. The purpose of this research is to design a set of furniture for the lounge area for visitors of Surabaya University Library as an effort to improve the function of facility in learning and research. In this research, the method used is qualitative method with IDI (In Depth Interview) on some librarians and visitors of Surabaya University Library, and observation done by observing around Surabaya University Library. From the results of the research, it will be designed a set of furniture for the lounge area of the table for ‘lesehan’ which features have a bookstrip and electric socket; as well as bookshelves that can accommodate books that have been borrowed by visitors, with the concept of modern design with a blend of futuristic concepts.